Follicular dysplasia of black hair in dogs: revier - De Carvalho Lima Gondim , Adriana (Pubvet, 2020)
Skin diseases are frequent causes of veterinary care at the small animal clinic. Black hair follicular dysplasia is a disease of inherited origin whose etiology has not yet been fully elucidated. This disease only affects the black coat of young dogs that have bi or tricolor coat. The diagnosis is made based on the patient’s history, clinical examination and complementary exams, such as trichogram and histopathological exam. Being a rare disease, this article aims to gather relevant information about the disease, alerting the veterinarian about its occurrence.